Articulation between knowledge operating levels and semiotic representation records in probability tasks (Research, Society and Development, 2020)
This article aims to investigate how the Levels of Functioning of Knowledge are linked to the Records of Semiotic Representations expected for tasks in the field of Probability. This articulation is the result of the theoretical study of a research developed and already concluded in a Professional Master's in Science and Mathematics Teaching. This is a qualitative research that refers to a bibliographic study carried out in the light of the theoretical approach of the Levels of functioning of knowledge expected by students and the theory of Semiotic Representation Records, which made it possible to understand the processes of understanding and solving tasks. This study made us infer that the task analysis constitutes a relevant path in the evaluation, teaching and learning process and contributes effectively to the understanding of the requirements of the scientific knowledge production process.